The Model Of Pedestrian Arrangement In The Commercial Area Corridor Of Dr. Mansur Street Medan City - Abdillah, Wahyu; Irsal; Harisdani, Devin Defriza; Hadinugroho, Dwi Lindarto; Novrial; Eddy, Firman (Talenta Publisher, 2025)
This study explores a pedestrian arrangement model in the commercial corridor of Dr. Mansur Street, Medan City, which exhibits characteristics of urban sprawl through a strip development pattern. The research seeks to answer the question: How can pedestrian infrastructure be arranged to improve spatial connectivity, social interaction, and place identity in commercial areas affected by urban sprawl? The approach refers to visual, structural, and collective linkage theories to design connected pedestrian spaces that reflect the local character. The spatial arrangement focuses on forming a street space that functions like an urban square, highlighting local elements and everyday community activities to strengthen the identity of the area. In line with the Strategic Plan of Universitas Sumatera Utara, which promotes the value of local wisdom, this research contributes to the development of planning strategies based on local values. The results show that the Dr. Mansur corridor has strong potential to serve as a social space that supports community interaction and enhances the quality of the urban environment. The proposed design applies the principles of smart growth, which integrates social, cultural, environmental, and local wisdom aspects in a holistic way. The findings are expected to serve as a reference for city governments and policymakers in designing public spaces that are adaptive to urban change and support community-based development. Keywords: pedestrian, arrangement, path, smart growth